Pengaruh Jenis Sumber Nutrisi dan Media Tanam terhadap Pertumbuhan dan Kualitas Hasil Microgreen Brokoli (Brassica oleracea var. italica Planck) - ZADE, SAKHARA; RAI, I NYOMAN; WIJANA, GEDE (Agrotrop : Journal on Agriculture Science; Vol 13 No 2 (2023)DO - 10.24843/AJoAS.2023.v13.i02.p14, 2023)
Effect of Nutrient Source Type and Planting Media on Growth and Yield Quality of Microgreen Broccoli ( Brassica oleracea var. italica Planck). The use of types of nutrient sources and planting media is the most important thing in the cultivation of microgreen broccoli which functions to support growth and development so as to get good yields.  The purpose of this study was to obtain the best types of nutrient source and growing media in increasing broccoli microgreen growth and yield. The study was designed factorial with 2 factors and 3 replications. The design used was a completely randomized design. The first factor was the type of planting medium which consisted of three levels i.e. rockwool, roasted husks and cocopeat while the second factor was the type of nutrient source which consisted of four levels i.e. without nutrient (control), goodplant, fermented liquid bamboo shoots extract and light green coconut water. The results showed that the interaction of goodplant nutrition and rockwool growing media produces the highest results in  economical microgreen fresh weight per plant, percentage of germination,  percentage of radicle growth,  percentage of plumule growth, percentage of institutional leaf growth,  microgreen stem length and vitamin C content than those of that others  treatment. Goodplant nutrition gave the best growth percentage of microgreen, percentage of seed emergence, lowest percentage of dead plants  compared to the use of nutrient solution fermented bamboo shoots extract and green coconut water nutrition. The use of rockwool planting media gave the besst  growth percentage, percentage of seed emergence, day the cotyledons rose to the surface of the media and the lowest percentage of dead plants compared with the use of roasted husk and cocopeat growing media.